True Patriot Love - Wieland, Joyce (Ottawa : The National Gallery of Canada, 1971)
The author has used a book published by The National Gallery of Canada entitles Flora of the Canadian Arctic Archipelago Bulletin#146 Series 50. as her base and superimposed pictures and text of her own. Miniature Canadian flag is pasted on inside front cover. Back cover has envelope with pink pamphlet, poster and map.
True Patriot Love / Véritable amour patriotique, The National Gallery of Canada, Ottawa, 1 July - 8 August 1971
Engels & Frans
kunstcatalogus
Keywords: Wieland, Joyce